PENERAPAN MICROSITE BERBASIS PBL PADA MATERI PENGELOLAAN KEUANGAN KELUARGA UNTUK MENINGKATKAN LITERASI DIGITAL DAN LITERASI FINANSIAL SISWA - Motiara, Ica; Adhi Suciptaningsih, Oktaviani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education is an important aspect in improving the quality of the Indonesian generation so that they can compete in this era of globalization, where it is very important to have skills in digital literacy and high financial literacy. However, based on data obtained from PIRLS, TIMSS, PISA and OJK, it shows that digital literacy and financial literacy skills among Indonesian students are still relatively low. This research aims to analyze the effectiveness of implementing a PBL (Problem Based Learning)-based microsite on family financial management material in increasing students' digital literacy and financial literacy. The microsite developed was created to present material on family financial management in accordance with PBL (Problem Based Learning) principles. The research method used is Classroom Action Research through action in cycle I and cycle II in the learning process. The research stages were carried out in accordance with research procedures, namely a) planning, b) implementation, c) observation, and d) reflection. The findings in this research show that the implementation of PBL-based microsites can increase students' digital literacy through the use of interactive technology and there is a significant increase in students' understanding of basic financial literacy concepts, such as financial management, investment and budget planning. This can be seen from the average student learning outcomes in family financial management material which has increased significantly by 93,9 and the completeness of student learning outcomes has increased by 93,75%. The practical implication of this research is the importance of paying attention to learning strategies that focus on learning experiences based on students' real-life needs and conditions.